Legal Considerations Settlement Of Criminal Acquisition Of Land - Hapshary Noor Diansaputri; Aryani Witasari (Universitas Islam Sultan Agung, 2020)
One of the land conflicts that often occurs is the grabbing of land belonging to other people, whether intentional or unintentional, either by an individual or by a group of people. Land grabbing is a form of taking the rights of others against the law. This study aims to identify and analyze the factors that cause land grabbing, to identify and explain the form of legal arrangements for the crime of land grabbing and to analyze judges' legal considerations on the settlement of land grabbing crimes. This study uses a normative juridical approach, which is a legal research conducted by examining library materials or secondary data as the basic material for research. The theory used to analyze law enforcement theory and dispute resolution theory. Based on the research, the conclusion is: The factors driving the crime of land grabbing are the lack of awareness of the importance of legal protection of land ownership or control rights among the community, the existence of parties with certain motives against land that are considered to have no legal protection. Crimes against land grabbing are also regulated in the Criminal Code (KUHP), which is regulated in several articles in the KUHP, including: Article 167 of the Criminal Code and Article 385 of the Criminal Code. In deciding a case, a judge must consider sociological, philosophical and juridical aspects.